2011
DOI: 10.1080/10668926.2012.619093
|View full text |Cite
|
Sign up to set email alerts
|

Academic and Social Integration and Persistence of International Students at U.S. Two-Year Institutions

Abstract: As a growing number of international students discover two-year institutions as the possible gateway to U.S. higher education, it is important to have a better understanding of who these students are, what attracts them to two-year colleges, and how they engage with the campus community. To address these questions, the study used the data from the Beginning Postsecondary Students Longitudinal Study (BPS:04=06) survey to examine the profile of international students attending two-year versus four-year instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 22 publications
(27 reference statements)
1
48
0
Order By: Relevance
“…A plethora of studies have been focused on international community college students' educational aspiration (Hagedorn & Lee, 2005;Mamiseishvili, 2011;Bohman, 2010).…”
Section: International Students In Community Collegesmentioning
confidence: 99%
See 2 more Smart Citations
“…A plethora of studies have been focused on international community college students' educational aspiration (Hagedorn & Lee, 2005;Mamiseishvili, 2011;Bohman, 2010).…”
Section: International Students In Community Collegesmentioning
confidence: 99%
“…The findings concluded that these international students were more academically transfer-ready than their non-international counterparts (Hagedorn & Lee, 2005). Furthermore, Mamiseishvili (2011) studied international students' persistence in community colleges by utilizing Beginning Postsecondary Students Longitudinal Study (BPS) data. In this study, faculty interaction and academic advising showed significant influence on first-to-second year persistence (Mamiseishvili, 2011).…”
Section: Recent Studies On International Students In Community Collegesmentioning
confidence: 99%
See 1 more Smart Citation
“…Student engagement in academic and social activities has long been recognized as a critical factor in shaping college outcomes (Astin, 1993;Burkholder, 2014;Harper & Quaye, 2009;Kuh, Cruce, Shoup, & Kinzie, 2008;Kuh, Kinzie, Buckley, Bridges, & Hayek, 2006;Kuh, Kinzie, Schuh, Whitt, & Associates, 2010;McClenney, 2006;Pascarella & Terenzini, 2005;Stebleton, Soria, Huesman, & Torres, 2014;Tinto, 1993;Ullah & Wilson, 2007;Zhao, Kuh, & Carini, 2005), however little is known about the patterns of academic engagement of international students at community colleges (Mamiseishvili, 2012).…”
Section: Problemmentioning
confidence: 99%
“…Although the overall upward trend in international student enrollment in the United States has been persistent over time, preferences for pathways have changed. Today, a growing number of international students consider American community colleges as a gateway to a higher education degree (Behroozi-Bagherpour, 2010;Mamiseishvili, 2012;Sallie, 2008). According to data collected by the IIE (2014c), the number of international students enrolled in community colleges increased by 7.4% from 81,869 in 2004-2005 to 87,963 in 2013-2014.…”
Section: Introductionmentioning
confidence: 99%